Esophageal manometry, esophagogastroduodenoscopy, and duodenal mucosal histopathology in systemic sclerosis - MB Adarsh; Shefali K Sharma; Kaushal K Prasad; Varun Dhir; Surjit Singh; Saroj K Sinha (JGH Open, 2019)
Background and Aim Systemic sclerosis (SSc) is known to involve the gastrointestinal (GI) tract, resulting in dysmotility, gastroesophageal reflux disease, and mucosal changes causing significant morbidity. The study aimed to assess esophageal motility and duodenal mucosal changes in SSc. Methods This is a prospective, cross‐sectional, single‐center study of 23 patients with SSc diagnosed on the basis of standard criteria. Clinical details including the GI symptoms were recorded. All of them underwent esophagogastroduodenoscopy with duodenal biopsy, and 21 underwent esophageal manometry. Results Regurgitation, heartburn, and dysphagia were seen in 19 (82%), 16 (69%), and 10 (43%) patients, respectively. On endoscopy, 19 patients (83%) showed changes of reflux esophagitis (4 had grade C esophagitis), and 3 had esophageal candidiasis. Of the 21 patients who underwent esophageal manometry, 13 (62%) had absent peristalsis, 6 (28%) had ineffective peristalsis, and 10 (48%) had hypotensive lower esophageal sphincter (LES). Duodenal biopsy showed partial villous atrophy in 9 (39%) patients, increased intraepithelial lymphocytes in 18 (78%), and excess of mononuclear inflammatory cells in lamina propria in 21 (91%). Partial villous atrophy was seen more commonly in those with abnormal esophageal peristalsis and a hypotensive LES. Conclusion Most of the patients with SSc had esophageal dysmotility in the form of absent peristalsis, ineffective esophageal peristalsis, and hypotensive LES. Histology of descending duodenum demonstrated partial villous atrophy and chronic inflammatory infiltrates in most of the patients with SSc.